Pregnancy Outcomes among Patients with Sickle Cell Disease in Brazzaville. (15th September 2020) - Galiba Atipo Tsiba, F. O.; Itoua, C.; Ehourossika, C.; Ngakegni, N. Y.; Buambo, G.; Potokoue Mpia, N. S. B.; Elira Dokekias, A.
Abstract : Introduction . Sickle cell disease (SCD) is one of the most common genetic diseases in the world. It combines, in its homozygous form, chronic hemolytic anemia, vasoocclusive complications, and susceptibility to infections. It is well known that the combination of pregnancy and sickle cell disease promotes the occurrence of complications that are sometimes fatal for the mother and/or the fetus. Objective . The objective of the current study was to compare pregnancy outcomes among women with SCD with those of women without the diagnosis of SCD. Materials and methods . It was a case-control study carried out in four maternity hospitals in Brazzaville in 2 years (July 2017–June 2019). It concerned 65 parturients with SS homozygous SCD. The mode of childbirth and maternal and perinatal morbidity and mortality were compared with those of 130 non-sickle cell pregnant women. Results . The average age was 27 years for SCD women and 31 years for non-SCD women. The average gestational age at delivery was 35 weeks for SCD women and 38 weeks for non-SCD women. From the logistic regression analysis using the comparison group as the reference group, there was excessive risk in SCD compared to non-SCD of infection (29.3% vs. 4.6%, OR = 21.7, 95% CI [7.6–62.7]; p = 0.001 ), cesarean (63% vs. 35.4%, OR = 3.1, 95% CI [1.6–5.7]; p = 0.001 ), prematurity (75.4% vs. 30.8%, OR = 8, 95% CI [3.0–23.2]; p = 0.001 ), low birth weight (52.3% vs. 16.1%, OR = 4.7, 95% CI [2.4–9.4]; p = 0.001 ), neonatal requiring admission to the intensive care unit (40.3% vs. 17.5%, OR = 3.2, 95% CI [1.6–6.3]; p = 0.01 ), and neonatal death (21.5% vs. 4.8%, OR = 4.3, 95% CI [1.5–12.2]; p = 0.01 ). Conclusion . The risk of pregnancy in patients with homozygous sickle cell anemia remains high, on both the maternal and fetal sides.